Biological and Molecular Effects of Trypanosoma cruzi Residence in a LAMP-Deficient Intracellular Environment - Oliveira, Anny Carolline Silva; Rezende, Luisa; Gorshkov, Vladimir; Melo-Braga, Marcella Nunes; Verano-Braga, Thiago; Fernandes-Braga, Weslley; Guadalupe, Jorge Luís de Melo; de Menezes, Gustavo Batista; Kjeldsen, Frank; de Andrade, Hélida Monteiro; Andrade, Luciana de Oliveira (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi invades non-professional phagocytic cells by subverting their membrane repair process, which is dependent on membrane injury and cell signaling, intracellular calcium increase and lysosome recruitment. Cells lacking Lysosome Associated Membrane Proteins 1 and 2 are less permissive to parasite invasion, however more prone to parasite intracellular multiplication. Several passages through a different intracellular environment can significantly change T. cruzi’s gene expression profile. Here, we evaluated whether one single passage through LAMP deficient (KO) or wild type (WT) fibroblasts could influence invasion ability of T. cruzi Y strain trypomastigotes in L6 myoblasts and WT fibroblasts. Parasites released from LAMP2 KO cells (TcY-L2-/-) showed higher invasion, calcium signaling and membrane injury rates, in L6 myoblasts, when compared to those released from WT (TcY-WT) or LAMP1/2 KO cells (TcY-L1/2-/-). On the other hand, TcY-L1/2-/- showed higher invasion, calcium signaling and cell membrane injury rates, in WT fibroblasts, compared to TcY-WT and TcY-L1/2-/-. Albeit TcY-WT presented an intermediary invasion and calcium signaling rates in WT cells, they induced lower levels of injury, reinforcing that protein signaling may also have a significant contribution to parasite induced calcium signals. These results clearly show that parasites released from WT or LAMP KO cells are distinct from each other. Additionally, these parasites’ ability to invade the cell may be distinct depending on which cell type they interact with. Since these alterations most likely would reflect differences among parasite surface molecules, we also evaluated their proteome. We identified few protein complexes, membrane and secreted proteins regulated in our dataset. Among those, some members of MASP, mucins, trans-sialidases and gp63 proteins family, which are known to play an important role during parasite infection and could correlate to TcY-WT, TcY-L1/2-/- and TcY-L2-/- biological behavior.